2021
DOI: 10.1093/nar/gkab1281
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide messenger (p)ppGpp is an anti-inducer of the purine synthesis transcription regulator PurR inBacillus

Abstract: The nucleotide messenger (p)ppGpp allows bacteria to adapt to fluctuating environments by reprogramming the transcriptome. Despite its well-recognized role in gene regulation, (p)ppGpp is only known to directly affect transcription in Proteobacteria by binding to the RNA polymerase. Here, we reveal a different mechanism of gene regulation by (p)ppGpp in Firmicutes: (p)ppGpp directly binds to the transcription factor PurR to downregulate purine biosynthesis gene expression upon amino acid starvation. We first i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 89 publications
0
25
0
Order By: Relevance
“…Accordingly, the amounts of PurM, PurQ, PyrB and PyrP proteins were increased in the stationary Rho + proteome ( S1 Table ). These differences might reflect the altered levels of (p)ppGpp and GTP in Rho + cells, as it has been shown that (p)ppGpp stimulates activity of PurR, the repressor of the pur operon [ 114 ], while GTP antagonizes the activity of PyrR, the repressor of the pyr operon [reviewed in 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the amounts of PurM, PurQ, PyrB and PyrP proteins were increased in the stationary Rho + proteome ( S1 Table ). These differences might reflect the altered levels of (p)ppGpp and GTP in Rho + cells, as it has been shown that (p)ppGpp stimulates activity of PurR, the repressor of the pur operon [ 114 ], while GTP antagonizes the activity of PyrR, the repressor of the pyr operon [reviewed in 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…Here, we found that regulation of GTP biosynthesis enzymes by (p)ppGpp is a key to the prevention of chloramphenicol lethality in B. subtilis (Figure 6). Given the conservation of GTP biosynthesis regulations in Firmicutes 32,36,38,43,44,46 , it is possible that similar protection mechanisms also apply to Firmicute pathogens such as E. faecalis, in which we also observed (p)ppGpp-dependent lethality by chloramphenicol (Figure 1D). On the other hand, Gram-negative bacteria such as E. coli do not appear to require (p)ppGpp to survive chloramphenicol 26 , indicating that Gram-negative bacteria have evolved different protection mechanisms against this antibiotic.…”
Section: Prevention Of Chloramphenicol Lethality Through (P)ppgpp-reg...mentioning
confidence: 80%
“…In B. subtilis, (p)ppGpp regulates many cellular processes, including DNA replication 34,35 , transcription 36 , ribosome biogenesis 37,38 and protein translation and secretion [39][40][41] . However, its most well-characterized effect in Gram-positive bacteria is the regulation of purine metabolism 31,36,37,[42][43][44][45][46][47] . In B. subtilis, (p)ppGpp inhibits purine biosynthesis enzymes GuaB, Gmk, HprT, and XprT, with a strong impact on GTP levels and viability 32 .…”
Section: (P)ppgpp Downregulates Gtp Levels To Prevent Chloramphenicol...mentioning
confidence: 99%
See 1 more Smart Citation
“…While there are common and conserved themes, the specific protein targets and regulatory mechanisms of (p)ppGpp may differ between different bacterial species. For example, while (p)ppGpp affects the global and regional transcription of Escherichia coli through the direct binding to the DksA and the RNA polymerase (RNAP) [ 6 ], it affects transcription by affecting the GTP level and binding to specific transcription factors, such as PurR [ 7 ] and MglA/SspA complex [ 8 ], in other bacteria. In addition, (p)ppGpp can reduce DNA proliferation by binding to DnaG (synthetase of the priming RNA required for DNA replication) [ 9 ], affecting the expression and stability of DnaA (replication initiation ATPase) [ 10 ] and modulating the supercoiling state of oriC [ 11 ].…”
Section: How Do Magic Spot and Alarmone Mediate Stringent Response?mentioning
confidence: 99%